Optimalisasi Pemeriksaan Antenatal sebagai Upaya Meningkatkan Kesehatan Ibu dan Anak - Intan Kumalasari; Meisa Dwi Putri; Syarif Julima; Sumira Sumira; M. Miftahul Hasani Dwi Putra; Siti Dian Fadhila (Lembaga Pengembangan Kinerja Dosen, 2025)
Maternal and child health (MCH) is a priority in health development, especially in preventing pregnancy complications that may endanger the lives of both mothers and babies. One way to reduce these risks is through routine antenatal care and early detection of complications. However, in some areas, pregnant women still lack understanding of the importance of regular antenatal checks. This community service activity aims to increase pregnant women’s knowledge about the importance of antenatal care and early detection of pregnancy complications at Posyandu Ester 24, a working area of Puskesmas Dua Puluh Tiga Ilir, Palembang, conducted from December 1 to 6, 2024. The activity involved counseling, free antenatal care checks, and training for healthcare workers. The results showed an improvement in pregnant women’s understanding of pregnancy danger signs and the importance of routine healthcare. Antenatal care successfully detected several health risk factors, such as anemia and chronic energy deficiency (CED), allowing for early intervention. Although the main challenge was motivating pregnant women to attend routine checks, the activity successfully increased participation in antenatal care and health education. It is hoped that this activity can serve as a model for other maternal and child health programs in the future.